Blood pressure variation and its association with outdoor temperature among adults with hypertension in a primary care setting in South Africa - Havyarimana, Enock (Department of Public Health and Family Medicine, 2019)
Rationale – There is limited evidence about the effect of climate on blood pressure management of people living with and cared for hypertension in Sub-Sahara Africa. We investigate the relationship between outdoor temperature and blood pressure in a primary care setting with limited control of indoor climate in Cape Town, South Africa. Method – The study uses blood pressure data from 2494 participants screened and enrolled for entry in the SMS-text Adherence (StAR) trial study. Participants’ data were matched with outdoor temperature and air quality data using the nearest hour of enrolment. Individuals were included in this study if they were recruited during the study’s screening period (June 2012 to November 2014) and the clinic’s operating hours (7h00 and 17h00). Result - 72% of participants enrolled for the trial were female and had a BMI of 31 kg/m2 . There was an inter-subject variation of blood pressure between participants enrolled in winter and spring. Those enrolled in winter (June – July) and in the morning (07h00-10h00) when temperatures were generally low, had a higher mean blood pressure compared to those enrolled during spring (September - November) and in the afternoons (≥13h00). Mean outdoor temperature during the trial period was 16.7°C (min: 3.7°C –max: 30.7°C) with lowest temperatures recorded in June. Both outdoor temperature and blood pressure were found to be associated with nitrogen dioxide (NO2) and sulphur dioxide and (SO2) and therefore may be confounded by them. In a multivariate analysis controlling for air pollution, humidity and several leading cardiovascular risk factors, it was observed that a 10°C increase in outdoor temperature was associated with 7.5mmHg (95% CI: 3, 82 - 11, 18) change in systolic blood pressure. This association is modified by age, BMI and the time of the day. Those 65 years and older, with a low BMI and those enrolled in the morning (7h00 – 10h00) had the greatest change in blood pressure due to outdoor temperature Conclusion –The study shows an inverse association between outdoor temperature and clinic-based blood pressure in a primary care setting in South Africa. Given the fact that clinic-based blood pressure measures are used to direct the management of hypertension, greater attention needs to be given to environmental factors which may affect it. This may become of greater clinical relevance with changes in the climate and extreme weather patterns, including extensive smog